LIVING HADIS: TRADISI REBO WEKASAN DI PONDOK PESANTREN MQHS AL-KAMALIYAH BABAKAN CIWARINGIN CIREBON - Siti Nurjannah (UIN Siber Syekh Nurjati Cirebon, 2017)
The rebo-wekasan tradition is one of the traditions which until now is still practiced by the Muslim community of Nusantara, both on the island of Java and outside Java. The tradition of rebo exertion in the archipelago is practiced with various rituals that are carried out, such as: prayer, prayer, pilgrimage, bathing and charity. But the diversity of these rituals has the same purpose, namely that the perpetrators be given salvation from all kinds of dangers and calamities especially those that are in the month of Safar. This study aims to reveal the history and practice of traditional ritual rebo rituals and explore religious texts originating from the Prophet's hadith which are guidelines or steps for Ya>si>n and santri in implementing the rebo wekasan tradition at MQHS Islamic Boarding School Al-Kamaliyah Babakan Ciwaringin Cirebon . This study uses the theory of living hadith, with a historical-theological approach and phenomenology. The method used is qualitative, and data collection techniques by conducting observations, interviews and documentation.